(untitled) (Journal of Hama University, 2022)
The concept of conservative endodontics has led to new endodontic access cavity designs that could leave some areas in the pulp chamber unprepared. A suggested solution for this problem is irrigation activation. While available literature denies the benefit of ultra-sonic activation method. There’s no available studies evaluating the efficacy of sonic activation in cleaning the chamber. The goal of this study is to evaluate how adding sonic activation of irrigation to the ultra sonic-internal heat dual activation method would affect the amount of pulp remnants in the orifice-directed-accessed pulp chamber using histological method. 30 mandibular molars where collected(N=30) and a CBCT have been made according to which the samble was divided into two groups(n=15) and access cavities were prepared using the measures taken from the scan. After root canals instrumentation the sodium hypochlorite irrigation solution was activated using heat and ultra-sonic activation in group 1 (H+US) while in group 2 (H+US+S) the irrigation solution was activated using heat, ultra-sonic activation and sonic activation by an Eddy tip mounted on a sonic scaler. Specimens were prepared for histological examination and the pulp tissue remnants space perception to the total space of the chamber was measured for all specimens. Data was analysed using Mann-Whitney analysis(P=.05). Pulp tissue remnants perception in H+US was significantly higher than in H+US+S(P<.05). It can be concluded that Sonic activation using polymer Eddy tip increases pulp chamber cleaning when Orifice-directed dentin conservation access cavity design is used.